IMPLEMENTATION AND CHALLENGES OF E-LEARNING AMONG ASNAF STUDENT IN PERLIS: A DESCRIPTIVE ANALYSIS - Mustafa, Wan Azani; Wan Muhamad, Wan Zuki Azman; Adnan, Ernie; Hanafi, Abdul Ghafur; Asni, Fathullah (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This study examines the implementation and challenges of e-learning among asnaf (zakat-eligible) students in Perlis, Malaysia, against the backdrop of national digital education initiatives accelerated by the COVID-19 pandemic. While Malaysia’s MyDIGITAL and Education Blueprint 2021–2025 emphasize digital equity, marginalized groups like the asnaf constrained by infrastructural gaps, limited digital literacy, cultural hesitations, and fragmented institutional coordination face persistent barriers. A quantitative descriptive analysis, utilizing a structured questionnaire administered to 105 purposively sampled asnaf students across three schools, revealed moderate to high awareness of e-learning tools (mean = 3.10, SD = 0.43), with 91.4% having device access, primarily smartphones. However, utilization remained inconsistent, with regular usage scoring lowest (mean = 2.77). Challenges included connectivity issues (mean = 2.40), lack of quiet study spaces (mean = 2.50), and limited digital skills (mean = 2.43), though anxiety (mean = 1.78) and institutional support gaps (mean = 1.96) were less pronounced. A significant negative correlation (r = -0.426, p < 0.001) between awareness and challenges underscored the potential of enhanced digital literacy to mitigate barriers. The findings highlight the need for culturally attuned, faith-aligned interventions that integrate zakat institutions with educational policies, prioritize localized digital training, and address infrastructural inequities. By bridging the disconnect between religious welfare systems and technocratic agendas, Malaysia can advance inclusive e-learning models that empower marginalized communities while aligning with national development goals.